2020
DOI: 10.21776/ub.rjls.2020.007.01.4
|View full text |Cite
|
Sign up to set email alerts
|

Plankton Community Structure as Bioindicator Trophic Status of Jatigede Reservoir Waters

Abstract: Jatigede Reservoir in Sumedang Regency is a land mass planning designed as a multi-function reservoir. The main water source for this reservoir is from Cimanuk River, which flows through Garut Regency, and has many industrial activities around the river flow. This research was conducted to assess the trophic status of water pollution in Jatigede Reservoir by utilizing plankton as a bioindicator agent. Samples were collected from 9 observation stations from November 2018 until January 2019. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…The Phytoplankton diversity index ranged from 1.44 -2.15, the evenness index 0.13 -1.33 and dominance index 0.40 -0.60 [14]. In 2018 research by Rosadi [15] there were 26 species of phytoplankton with an abundance of 4,186 ind/l, diversity index ranged 0.53 -1.60, evenness index ranged 0.25 -0.71, and dominance index ranging from 0.27 -0.77. In 2019 there were 11 species of phytoplankton with an abundance of 111,106 ind/l with a diversity index 0.105 -2.010 and an evenness index ranged 0.20 -0.26 [16].…”
Section: Water Conditions Of Jatigede Reservoirmentioning
confidence: 99%
See 2 more Smart Citations
“…The Phytoplankton diversity index ranged from 1.44 -2.15, the evenness index 0.13 -1.33 and dominance index 0.40 -0.60 [14]. In 2018 research by Rosadi [15] there were 26 species of phytoplankton with an abundance of 4,186 ind/l, diversity index ranged 0.53 -1.60, evenness index ranged 0.25 -0.71, and dominance index ranging from 0.27 -0.77. In 2019 there were 11 species of phytoplankton with an abundance of 111,106 ind/l with a diversity index 0.105 -2.010 and an evenness index ranged 0.20 -0.26 [16].…”
Section: Water Conditions Of Jatigede Reservoirmentioning
confidence: 99%
“…The zooplankton evenness index ranged from 0.40 -0.60 and the dominance index ranged from 0.30 -0.50 [14]. In 2018 the number of zooplankton species was 6 species with a total abundance of 21 ind/l and a diversity index ranging from 0.00 -0.76, evenness index 0.00 -0.82, and dominance index 0.00 -0.50 [15]. Research by Angkasa [21] related to zooplankton in the Jatigede Reservoir in 2019 showed that there were 23 types of zooplankton species with a total abundance of 11,146.…”
Section: Water Conditions Of Jatigede Reservoirmentioning
confidence: 99%
See 1 more Smart Citation
“…The abundance of plankton supports the growth and development of fish biota in aquatic habitats. The presence of plankton in the waters is also influenced by water quality [6]. The abundance and diversity of plankton can be used as water indicators [7].…”
Section: Introductionmentioning
confidence: 99%